Injectable Hyaluronic Acid Hydrogel Containing Platelet Derivatives for Synovial Fluid Viscosupplementation and Growth Factors Delivery - Toropitsyn, Evgeniy; Ščigalková, Ivana; Pravda, Martin; Velebný, Vladimír (Macromolecular bioscience, 2023)
Osteoarthritisis a highly prevalent musculoskeletal disorder characterized by degradation of cartilage and synovial fluid (SF). Platelet derivatives as platelet-rich plasma (PRP) and platelet lysate have great potential in the treatment of osteoarthritis because they contain biologically active substances including growth factors (GFs). Rapid release of GFs and their short biological half-life are factors that can limit the therapeutic impact of PRP therapy. Herein, the first work that describes hydrogels based on polyaldehyde derivative of hyaluronic acid (HA-OX) as carriers of platelet derivatives for in situ applications is presented, which can be a possible solution to the problem. HA-OX hydrogels containing 50% (w/w) of PRP or platelet lysate can be injected using a syringe due to low viscosity(<10 Pa s) and injection force (<20 N), and reach elastic modulus up to 2000 Pa. Insulin-like GF-1 and Platelet-derived GF-AB release from HA-OX hydrogels (mesh size 297-406 nm) by Fickian and non-Fickian diffusion respectively. The released PRP GFs maintain their ability to induce cell proliferation (87%-92%). Based on the obtained results, the unique concept of a new material that can restore viscoelastic properties of SF and at the same time gradually deliver GFs from platelet derivatives is designed.
Keywords: viscoelastic properties; plazma bohatá na destičky; Hyaluronic Acid; chrupavka; Hydrogels; osteoarthritis; platelet derivatives; Platelet-Rich Plasma; viskosuplementace; hydrogels; Synovial Fluid; hydrogely; Intercellular Signaling Peptides and Proteins; Viscosupplementation; mezibuněčné signální peptidy a proteiny; synoviální tekutina; Cartilage; kyselina hyaluronová; controlled releases